1995
DOI: 10.1002/nml.4130060205
|View full text |Cite
|
Sign up to set email alerts
|

Accountability and nonprofit organizations: An economic perspective

Abstract: A popular concern is whether the managers of nonprofit enterprise are accountable. This article considers accountability in the context of three questions. First, how do groups establish a basis on which to hold managers acountable? Second, to whom should a manager be accountable? Third, can a person or group make it important to a manager to act in the best interests of the person or group? These three questions are addressed by the fields of public choice theory, social choice theory, and principal‐agent the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
1

Year Published

1996
1996
2010
2010

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 49 publications
(24 citation statements)
references
References 3 publications
0
23
0
1
Order By: Relevance
“…The discussion here focuses primarily on principal-agent theory, although it should be noted that public choice theory has extensively examined how and why interest groups form, the processes through which they communicate and enforce their desires, and how they deal with free riders (see, for example, Mueller, 1989;Olson, 1965). Relatedly, social choice theory has investigated people's interactions in the political arena, detailing, for example, the inherent complexities of making collective decisions (Arrow, 1963;Bogart, 1995).…”
Section: Economic Perspectivesmentioning
confidence: 98%
See 2 more Smart Citations
“…The discussion here focuses primarily on principal-agent theory, although it should be noted that public choice theory has extensively examined how and why interest groups form, the processes through which they communicate and enforce their desires, and how they deal with free riders (see, for example, Mueller, 1989;Olson, 1965). Relatedly, social choice theory has investigated people's interactions in the political arena, detailing, for example, the inherent complexities of making collective decisions (Arrow, 1963;Bogart, 1995).…”
Section: Economic Perspectivesmentioning
confidence: 98%
“…While business organizations are accountable primarily to shareholders, nonprofits are expected to respond to the interests of their donors, boards, clients, and contracting agencies (Bogart, 1995). Najam (1996) has observed that NGOs are accountable to multiple actors: to patrons, clients, and themselves.…”
Section: Principal-agent Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…Applying economic theory to nonprofits, Bogart (1995) suggested that accountability implies identifying constituencies or groups to whom the organization owes compliance, specifying the interests of those groups, and communicating information about how well the organization is serving those interests. Lawry (1995) presented an ethical framework for nonprofit accountability that emphasized similar issues: identifying to whom accountability is due, understanding and reconciling expectations that may be both legitimate and divergent, setting reasonable standards, providing accessible information by which to assess compliance, and modeling or demonstrating integrity in decisions and actions.…”
Section: Hollandmentioning
confidence: 99%
“…"We try to avoid even the appearance of self-dealing in our work and to remain impartial and objective in our decision making, so we can sustain others' trust and confidence in us" As Bogart (1995) recommended, a few boards sent out periodic reports to staff, sponsors, and other stakeholders, telling them of the board' s goals and inviting their feedback on its work. "We send out progress reports every year.…”
Section: Identifying and Staying Focused On Prioritiesmentioning
confidence: 99%